Petrogenesis and tectonic environment of Neoproterozoic calc-alkaline magmatism in the southern portion of Socorro-Guaxupé Nappe: comparative study of pre-collisional orthogneisses and post-collisional granitoids - Toledo, Bárbara Bueno (2024)
The Socorro-Guaxupé Nappe (SGN) is a high-metamorphic grade allochthonous terrane situated in southeast Brazil, believed to be a segment of a Late Neoproterozoic magmatic arc that developed along the active margin of a continental plate. Extending over 20 km, the SGN exposes a crustal section containing granulites, migmatites, and charnockites in its lower segments (~8-10 kbar). In the upper portions (~4-5 kbar), migmatitic para- and orthogneisses are intruded by younger Neoproterozoic (630580 Ma) granites. Dating the complete set of (meta)-plutonic rocks in the Socorro Domain, the southern segment of the SGN, using U-Pb zircon SHRIMP and LA-ICP-MS techniques, reveals a chronological sequence. This sequence begins with various types of charnockites and orthogneisses (650-640 Ma) intruding the lower granulites, leading to the formation of the extensive Socorro Batholith (~620-610 Ma). The batholith is characterized by high-K calc-alkaline (HKCA) porphyritic biotite-hornblende granitoids with intermediate SiO2 contents (60-68 wt%), penetrating the middle to upper part of the crustal section at emplacement pressures of ~5-6 kbar. Anatectic granites, originating from para- and orthogneisses in the upper section, indicate two prominent episodes of crustal melting at 625 and ~605 Ma, marking the final phase of syn-orogenic magmatism. Post-orogenic A-type granites (~580 Ma) invade the southern part of the Socorro Domain and are linked to orogen collapse. Notably, there is a significant decline in Ndt from -4 to -6 in the older and deeper orthogneisses and charnockites to the shallower HKCA granitoids (Ndt < -12), coinciding with the decrease in age. This pattern suggests an upward-propagating magma column incorporating partial melts from rocks with a more extended crustal residence in the middle and upper sections of the SGN crustal profile.